2021
DOI: 10.3390/ijms22179183
|View full text |Cite
|
Sign up to set email alerts
|

CRKL, AIFM3, AIF, BCL2, and UBASH3A during Human Kidney Development

Abstract: We aimed to investigate the spatio-temporal expression of possible CAKUT candidate genes CRKL, AIFM3, and UBASH3A, as well as AIF and BCL2 during human kidney development. Human fetal kidney tissue was stained with antibodies and analyzed by fluorescence microscopy and RT-PCR. Quantification of positive cells was assessed by calculation of area percentage and counting cells in nephron structures. Results showed statistically significant differences in the temporal expression patterns of the examined markers, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…This suggests a potential role for UBASH3A in the regulation of protein interactions and the ubiquitinproteasome system, which is crucial for cellular homeostasis and development. There is only one paper by Lozic et al from our group, who describe UBASH3A expression patterns in different structures of the developing human kidney [6]. We found that the UBASH3A protein was observed as punctate, with mostly nuclear staining in developmental kidney tubules and glomeruli.…”
Section: The Ubash3 Signalling Pathway In Mammalian Developmentmentioning
confidence: 43%
See 1 more Smart Citation
“…This suggests a potential role for UBASH3A in the regulation of protein interactions and the ubiquitinproteasome system, which is crucial for cellular homeostasis and development. There is only one paper by Lozic et al from our group, who describe UBASH3A expression patterns in different structures of the developing human kidney [6]. We found that the UBASH3A protein was observed as punctate, with mostly nuclear staining in developmental kidney tubules and glomeruli.…”
Section: The Ubash3 Signalling Pathway In Mammalian Developmentmentioning
confidence: 43%
“…However, their roles in development are less studied. UBASH3 proteins have been found to have implications in certain developmental processes [6]. They might influence cell fate decisions or signalling events that are critical for proper embryonic development, although 2 of 14 the specific mechanisms are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of Cep63 and Smarcal1 might affect osteoporotic BMSCs viability and the mechanisms deserved more study. Aifm3 (apoptosis inducing factor mitochondria associated 3, also known as AIFL) induces cell apoptosis in a caspase-dependent manner by changing the oxidoreductase activity and mitochondrial membrane potential 43 . It's reported that MSC-derived exosomes protect cardiomyocytes from apoptotic cell death via downregulated Aifm3 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The temporo-spatial expression of single CAKUT candidate genes has been determined by antibody staining and RT-PCR in human fetal kidney tissue. Analysis of the expression data allowed the conclusion of each candidate gene’s role in renal development [14, 15]. Moreover, multiple studies evaluated sc-mRNA expression in kidneys.…”
Section: Discussionmentioning
confidence: 99%